PENGARUH PEMAHAMAN PELAKU UKM DALAM MENYUSUN LAPORAN KEUANGAN TERHADAP IMPLEMENTASI LAPORAN KEUANGAN BERDASAR SAK ETAP DENGAN PERSEPSI PELAKU UKM SEBAGAI MODERATING VARIABLE - Febrianty, Febrianty; Divianto, Divianto (Universitas Pendidikan Ganesha, 2017)
The purpose of this research is to know: a). The magnitude of the influence of SME Understanding Factors in preparing financial statements based on SAK-ETAP on the implementation of financial statements based on SAK-ETAP, b). The magnitude of the effect of the use and ease of use of financial statements under SAK-ETAP moderate against the implementation of financial statements based on SAK-ETAP. The independent variable is the understanding of SMEs in preparing financial statements and the dependent variable is the Implementation of Financial Statements. While moderating variable is perception of perpetrator of SME. The population in this study are all SMEs registered in BPS Palembang City amounted to 32,706 based on data in 2015. The sample of this study is SMEs in Sukarami District in Palembang City a number of 30 SMEs. The data were collected using questionnaires. Analyzer used to test H1 used simple linear regression model. While H2 - H3 tested with MRA (Moderated Regression Analysis). The results showed that the Influence of Understanding SMEs in Preparing Financial Statements based on SAK-ETAP on Implementation of Financial Statements in this study amounted to 0.747 or 74.7%. Interaction of Understanding SMEs in Preparing Financial Statements based on SAK-ETAP with the use of financial statements have a positive and significant impact on Implementation of Financial Statements (simultaneously) so that Hypothesis 2 supported. Interaction of Understanding SMEs in Preparing Financial Statements based on SAK-ETAP with the ease of use of financial statements have a positive and significant impact on Implementation of Financial Statements (simultaneously) so that Hypothesis 3 is supported.Â Keywords: Understanding, SME, financial statements, SAK ETAP